Efeito protetor dos extratos de Ascaris suum e Coccidioides posadasii e da lectina da semente de Dioclea violacea na artrite por zymosan em ratos e camundongos - Leite, Ana Karine Rocha de Melo (2009)
The interactions between innate and acquired immune responses participate in the pathophysiology of the autoimmune diseases. Though infections are associate with the development of the chronic arthritis it is possible that exposure to some germs as helminthes and fungi influences potentially the prevalence and/or gravity of the immune diseases. Lectins derivate of the plants can modulate the inflammation by action in receptors of the innate response. We investigated the effect of extracts from Ascaris suum (AS), Coccidioides posadasii (CS) and a lectin isolated from Dioclea violacea (Dviol) in zymosan-induced arthritis (ZyA). Wistar rats and Swiss mice received 1 mg or 0.1 mg zymosan intra-articular (i.art.), respectively. Groups were pretreated (30 min) with AS (0.25 - 2.5 mg/animal; i.p. or p.o.) CP (1 - 100 µg/animal; i.art. i.p. or p.o) or Dviol (0.3 - 30 µg; i.art. or 1 - 6 mg/kg; i.v.). Non-treated group (NT) received Zy (i.art.) and the vehicle. Naive animals received just saline (i.art.) and the vehicle. The hypernociception was evaluated through articular incapacitation test in s/1min. The joint exudate was used for evaluation of cell influx (CI), nitrite and cytokine levels. The synovium was used for histopatology. The glycosaminoglycan (GAG) content of the cartilage was quantificated for the measured of the structural damage. The AS extract both i.p. and p.o. significantly and dose-dependently inhibited CI and hypernociception in ZyA as compared to NT (P<0.01) as well as reverted articular damage assessed by quantification of the GAG and by synovitis observed in the histology. The administration of the AS extract reduced significantly levels of nitrite, interleukin-1β (IL-1β) and IL-10, but not tumor necrosis factor alpha (TNF-α) as compared to NT. In mice, it reduced IL-10 but not IL-1β and TNF- α. The treatment with CP extract both i.p. and p.o. inhibited hypernociception and CI in ZyA as compared to NT, but not reverted articular injury measured by GAG and histology. The administration of the Dviol in naïve animals promoted CI significant, though just the highest dose (30 g) promoted hypernociception. In ZyA, Dviol (i.art.) reduced the CI and hypernociception dose-dependently (P<0.01). The administration of Dviol (i.v.) significantly reduced both the hyperalgesia and CI in ZyA as compared to NT (P<0.01). The effect of the Dviol was reverted when it was pre-incubated with mannose (1M). The date show that AS extract promote functional improve and protect of the articular damage in ZyA that are associate with reduction of the NO and cytokine (i.art.) liberation. This effect is species independent and functions orally. An extract of the fungi CP has anti-inflammatory activity in ZyA. A lectin isolated of the Dviol reduces CI and hypernociception in ZyA probably by coupling the mannose receptor. Together the results show that substances that act in receptors of the innate response modulate the immunomediate articular inflammation.